Comparative Analysis Of PT Pegadaian's Financial Performance Before And After It Was Acquisited By PT Bank Rakyat Indonesia (Persero) TBK - Dwi Wuryantadi; Dudi Rudianto (Jurnal Scientia, 2024)
This research aims to compare the financial performance of PT Pegadaian before and after its acquisition by PT Bank Rakyat Indonesia (Persero) Tbk. The data source in this research is secondary data in the form of company financial reports obtained through the PT Pegadaian website. The sample in this research is the profitability ratio of PT Pegadaian in 2018 and 2019 before the acquisition and in 2022 and 2023 after PT Pegadaian was acquired by PT Bank Rakyat Indonesia (Persero) Tbk. The type of research used was quantitative descriptive and different tests and used the Wilcoxon signed rank test and Kruskal Wallis analysis techniques. The research results found that the acquisition strategy policy turned out that PT Pegadaian's financial performance before and after being acquired by PT Bank Rakyat Indonesia (Persero) Tbk had no significant differences either partially or simultaneously in terms of the profitability ratio with the Return On Assets (ROA), Return On indicators. Equity (ROE), Operating Expenses to Operating Income (BOPO), Net Interest Margin (NIM), Net Operating Margin (NOM), Equity to Paid-in Capital Ratio and Profit Component Performance.